The Effect of Physical Educational Class in Identifying Physical and Verbal Aggressive Behavior for the Ninth Grade Class in the Governorate of Karak - Hisham Aldmour; Raghda Aranki; Subhi Qablan; Taha Tarawneh (My University, 2011)
The purpose of the study is to identify both physical and verbal aggressive behavior during the physical educational class, for the 9th grade students. A random cluster sample of 330 students was selected from the education directorate in Karak governorate (165 females and 165 males). To reach the objectives of the study a questionnaire of 30 items was developed as a tool to collect data, and distributed over two dimensions; physical aggression and verbal aggression. The statistical methods used were: mean, standard deviation, and correlation. The results of the study were as follows: 1) Moderate aggressive behavior both verbally and physically as the percentage of the physical aggression is 2.14 and verbal aggression is 2.13 out of 4 points. 2) There is a correlation between the verbal and physical aggression with a coefficient of 0.74. The study recommends developing and enhancing the physical educational curriculum so as to absorb the students’ potentials and vent them out properly through participations in sports and safe activities, which would allow students to attain emotional balance.

هدفت الدراسة الحالية إلى الكشف عن السلوك العدواني بشقيه المادي واللفظي لدى طلبة الصف التاسع الأساسي داخل حصة التربية الرياضية، وقد تم اختيار عينة الدراسة بالطريقة العشوائية العنقودية، من طلبة الصف التاسع الأساسي في مديرية التربية والتعليم لمحافظة الكرك، وتكونت العينة من (330) طالبا وطالبة، منهم (165) طالبا، و(165) طالبة، ولتحقيق هدف الدراسة تم بناء استبانة كأداة لجمع البيانات والمعلومات، وقد تكونت الاستبانة من (30) فقره موزعه على بعدين: الأول العدوان المادي، والثاني العدوان اللفظي. وقد تم استخدم التحليلات الإحصائية التالية: المتوسط الحسابي، والانحراف المعياري، ومعامل الارتباط. وقد أظهرت نتائج الدراسة ما يلي: - وجود نسبة متوسطة من السلوك العدواني بشقيه المادي واللفظي، حيث بلغت نسبة السلوك العدواني المادي 2.14 ونسبة السلوك العدواني اللفظي 2.13 من أصل 4 درجات. - وجود علاقة ارتباطيه بين السلوك العدواني اللفظي والمادي بمعامل ارتباط 0.74. وأوصت الدراسة بضرورة تطوير مناهج التربية الرياضية لتتمكن من استيعاب طاقات الطلبة، وتفريغها بشكل صحيح من خلال المشاركة في الألعاب الرياضية والأنشطة غير الضارة، والتي تمكن الطلبة من المحافظة على اتزانهم الانفعالي.
أثر حصة التربية الرياضية في الكشف عن السلوك العدواني اللفظي والمادي لدى طلبة الصف التاسع الأساسي في محافظة الكرك